Eksplorasi Nuansa Teologis Dalam Tafsīr Al-Baiḍāwī - Ahady, Abdurrahman; Zulheldi, Zulheldi (Institut Agama Islam Sumatera Barat Pariaman, 2025)
The intellectuality of a mufasir influences his tendency in interpreting the Qur'an. Although this tafsir book has various styles, al-Bai??wi seems to have theological tendencies that are manifested in his tafsir. This study aims to examine the theological nuances presented by al-Bai??wi in his tafsir and analyze the characteristics and methodology of his tafsir. This research uses literature with a historical-factual approach model to reveal the philosophical conception of the tafsir figure in his work and the inductive method to see the systematic method used by the mufasir in formulating his work. The results of this study indicate that al-Baidhawi's interpretation methodology in his work Tafs?r Anw?r al-Tanz?l wa Asr?r al-Ta'w?l uses the tahil?li (analytical) approach by combining tafs?r bi al-ra'y and bi al-ma'??r. His interpretation is characterized by linguistic, fiqh, and 'aq?dah (theological). Regarding theological nuances as one of the main points of study in this article, it can be concluded that Tafsir al-Bai??wi, which is influenced by the theological school of ahl al-sunnah wa al-jam?'ah, especially the Asy'?riyyah - al-Bai??wi emphasizes the rejection of literal interpretation (tajs?m) of God's attributes by maintaining a balance between the text of the Qur'an and avoiding anthropomorphism. Although al-Zamakhshari's thoughts are widely used by al-Bai??wi in his tafsir, the Muktazilah ideology in al-Zamakhshari's Tafsir is abandoned by al-Bai??wi, and al-Bai??wi even criticizes the Muktazilah theological school.